Solution of Gear Ring Fracture of the Built-in Gear Pump of Automatic Transmission - Yang Weiwei; Yang Yaodong (Jixie chuandong)
In order to solve the problem that the gear ring fracture of gear pump without unloading groove,by using 3D modeling software,a gear pump model is established. The maximum trapped oil pressure of gear pump with no unloading groove,symmetrical unloading groove and bias type unloading groove are obtained through the internal flow field simulation with FLUENT,then the volumetric efficiency of the three pumps are calculated,the fact that using gear pump with bias type unloading groove can be a good solution to solve the problem of trapped oil and improve volumetric efficiency of the pump is verified. By calculating,the bias position of unloading groove is designed,and the prototype testing verification is carried out. Through comparing,the simulation results are similar to the test results,and a reference for the design of the built- in gear pump is provided.